FANDOM


\(X = \omega\)

\(X+1 = \omega+1\)

\(X+\alpha = \omega+\alpha\)

\(2X = 2 \omega\)

\(2X+\alpha = 2 \omega+\alpha\)

\(\alpha * X = \alpha \omega\)

\(\alpha * X + \beta = \alpha \omega+\beta\)

\(X^{2} = \omega^{2}\)

\(X^{2}+\alpha = \omega^{2}+\alpha\)

\(X^{3} = \omega^{3}\)

\(X^{\alpha} = \omega^{\alpha}\)

\(X^{X} = \omega^{\omega}\)

\(X^{X}+1 = \omega^{\omega}+1\)

\(X^{X}+\alpha = \omega^{\omega}+\alpha\)

\(2X^{X} = 2 \omega^{\omega}\)

\(2X^{X} + \alpha = 2 \omega^{\omega} + \alpha\)

\(\alpha * X^{X} = \alpha \omega^{\omega}\)

\(\alpha * X^{X} + \beta = \alpha \omega^{\omega} + \beta\)

\(X^{X+1} = \alpha \omega^{\omega+1}\)

\(\alpha * X^{X+1} = \alpha \omega^{\omega+1}\)

\(\alpha * X^{X+1} + \beta = \alpha \omega^{\omega+1} + \beta\)

\(X^{X+\alpha} = \omega^{\omega+\alpha}\)

\(\alpha * X^{X+\beta} = \alpha \omega^{\omega+\beta}\)

\(\alpha * X^{X+\beta} + \gamma = \alpha \omega^{\omega+\beta} + \gamma\)

\(X^{2X} = \omega^{2 \omega}\)

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.